Boundary values of the solutions of the parabolic equation - Lichawski, Kazimierz (Annales Mathematicae Silesianae, 1985)
The paper deals with the problem of the behaviour of a given solution of a quasi-linear parabolic equation near the parabolic boundary. Necessary and sufficient conditions for weak and strong convergence in the Sobolev space Wp1,1, p ≥ 2, are given.